Food-Grade Expression of Manganese Peroxidases in Recombinant Kluyveromyces lactis and Degradation of Aflatoxin B1 Using Fermentation Supernatants - Xia, Yu; He, Rui; Sun, Ying; Zhou, Hangyu; Gao, Minjie; Hu, Xiuyu; Cui, Xiaobing; Cheng, Qianqian; Wang, Zhouping (Frontiers in Microbiology, 2022)
Aflatoxins are naturally occurring high-toxic secondary metabolites, which cause worldwide environmental contaminations and wastes of food and feed resources and severely threaten human health. Thus, the highly efficient methods and technologies for detoxification of aflatoxins are urgently needed in a long term. In this work, we report the construction of recombinant Kluyveromyces lactis strains GG799(pKLAC1-Phsmnp), GG799(pKLAC1-Plomnp), GG799(pKLAC1-Phcmnp), and then the food-grade expression of the three manganese peroxidases in these strains, followed by the degradation of aflatoxin B1 (AFB1) using the fermentation supernatants. The expression of the manganese peroxidases was achieved in a food-grade manner since Kluyveromyces lactis is food-safe and suitable for application in food or feed industries. The inducible expression process of the optimal recombinant strain GG799(pKLAC1-Phcmnp) and the aflatoxin B1 degradation process were both optimized in detail. After optimization, the degradation ratio reached 75.71%, which was an increase of 49.86% compared to the unoptimized results. The degradation product was analyzed and determined to be AFB1-8,9-dihydrodiol. The recombinant strain GG799(pKLAC1-Phcmnp) supernatants degraded more than 90% of AFB1 in the peanut samples after twice treatments. The structural computational analysis for further mutagenesis of the enzyme PhcMnp was also conducted in this work. The food-grade recombinant yeast strain and the enzyme PhcMnp have potential to be applied in food or feed industries.